The use of veterinary drugs and vaccines in Turkey - Çagirgan H. (The use of veterinary drugs and vaccines in Mediterranean aquaculture, 2009)
Aquaculture is a relatively new industry for Turkey in comparison with terrestrial animals that started with rainbow trout culture in the 1970s. Turkey is the fifth biggest aquaculture producer in the Mediterranean, after Spain, France, Italy and Greece. Main cultured fish species are rainbow trout, sea bass and sea bream. Lactococcus garvieae infection, ERM, listonellosis and RTFS are the major diseases of rainbow trout, and IPNV and VHS have also been diagnosed. Vibriosis, pasteurellosis and tenacibaculosis are serious threatening bacterial infections of sea bass and sea bream. The most important parasites for cultured sea bass and/or sea bream are Cryptobia sp., Trichodina sp., Cryptocaryon irritans, Amyloodinium ocellatum, Myxidium spp., Diplectanum aequans, Meinertia oestroides, Lernanthropus kroyeri, Caligus minimus, and Furnestinia echeneis. Fish vaccines are imported but vibriosis, lactococcosis and ERM vaccines are also produced by a private company. Medicines containing oxytetracycline, potentiated sulphonamide, and florphenicol are produced for fish species. Turkey follows EC regulations, including 2377/90 and those related to chemotherapeutant residues. VHS, IHN, SVC and BKD are notifiable fish diseases.
The Use of Veterinary Drugs and Vaccines in Mediterranean Aquaculture, 2003/05/21-23, Izmir (Turkey)